Employing diffusion of innovation theory for ‘not missing the mass’ in community-engaged research - Tanvir C Turin; Nashit Chowdhury; Nahid Rumana; Mohammad Ali Ashraf Lasker; Mashrur Kazi (BMJ Open, 2023)
Introduction Engaging with minority communities, such as immigrants and ethnic minorities, often involves adopting top-down approaches, wherein researchers and policymakers provide solutions based on their perspective. However, these approaches may not adequately address the needs and preferences of the community members, who have valuable insights and experiences to share. Therefore, community-engaged approaches, which involve collaborative partnerships between community members and researchers to identify issues, co-create solutions, and recommend policy changes, are becoming more recognized for their effectiveness and relevance. Yet, prevailing community engagement efforts often focus on easily reachable and already engaged segments of the community, sometimes overlooking the broader population.Methods When working with immigrant and racialized communities, we encountered difficulties in engaging the wider community through traditional researcher-led approaches. We realized that overcoming these challenges required innovative strategies rooted in community-based participatory research principles and the diffusion of innovation theory. We recognized that a nuanced understanding of the community's dynamics and preferences was crucial in shaping our approach and building trust and rapport with the community members.Results The need to bridge the gap between researcher-led initiatives and community-driven involvement has never been more pronounced. Our experience, chronicled in this article, highlights the journey of our research program with an immigrant/racialized community. This reflection enhances our comprehension of community engagement that deliberately strives to reach a larger cross-section of the community. By providing practical methods for reaching the broader community and navigating the intricacies of engagement, we aim to assist fellow researchers in conducting effective community-engaged research across various minority communities.Conclusion In sharing our insights and successful strategies for community engagement, we hope to contribute to the field's knowledge. Our commitment to fostering meaningful collaboration underscores the importance of co-creating solutions that resonate with the diverse voices within these communities. Through these efforts, we envision a more inclusive and impactful approach to addressing the complex challenges faced by minority populations.